2018
DOI: 10.1103/physrevd.97.055041
|View full text |Cite
|
Sign up to set email alerts
|

UV-IR mixing in nonassociative Snyder ϕ4 theory

Abstract: Using a quantization of the nonassociative and noncommutative Snyder ϕ 4 scalar field theory in a Hermitian realization, we present in this article analytical formulas for the momentum-conserving part of the one-loop two-point function of this theory in D-, 4-, and 3-dimensional Euclidean spaces, which are exact with respect to the noncommutative deformation parameter β. We prove that these integrals are regularized by the Snyder deformation. These results indicate that the Snyder deformation does partially re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 64 publications
(118 reference statements)
0
24
0
Order By: Relevance
“…In this way, the free scalar field theory in the Hermitian realization (3) has been developed in [43], where it was shown that it is equivalent to the standard commutative theory. The interacting φ 4 theory has been investigated in a linear approximation in β in [44] and in the full β dependence in [63]. Of course, the interacting theory is no longer equivalent to its commutative counterpart.…”
Section: Outlook and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the free scalar field theory in the Hermitian realization (3) has been developed in [43], where it was shown that it is equivalent to the standard commutative theory. The interacting φ 4 theory has been investigated in a linear approximation in β in [44] and in the full β dependence in [63]. Of course, the interacting theory is no longer equivalent to its commutative counterpart.…”
Section: Outlook and Discussionmentioning
confidence: 99%
“…This fact makes the computation of these diagrams particularly difficult. A partial evaluation has been performed in [63], where it has been shown that the Snyder star product can introduce a natural regularization on at least some of the one-loop diagrams of the two-point functions. However, in the limit of vanishing incoming momenta, a variant of the UV/IR mixing of noncommutative field theory [7,8,64] appears.…”
Section: Outlook and Discussionmentioning
confidence: 99%
“…However, in spite of several attempts using various methods [14][15][16][17][18][19][20][21], the issue of finiteness of the Snyder field theory has not been established up to now. Here, we review an attempt to investigate this topic using the formalism of noncommutative QFT [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Attempting instead a calculation at all orders in , not all diagrams can be explicitly computed [24]. It can be shown, however, that the divergences are suppressed with respect to the noncommutative theory, and there are even indications that the integrals might be finite, at least for the interaction (34).…”
mentioning
confidence: 99%
“…The role of supersymmetric Yang-Mills theory in the noncommutative UV/IR mixing [17,18,[22][23][24] were extensively scrutinized to overcome the divergences which appeared in the field non-local interaction. Other class of NC theories namely, non-geometric theories like κ-Minkowski spacetime and Snyder spacetime also exhibits the UV/IR mixing at one-loop level [25,27,28]. In general, the UV/IR mixing is the universal property of all NCQFT.…”
Section: Introductionmentioning
confidence: 99%